European Perspectives: Prospects for Transport Research under the European Sixth Framework Programme - Stead, Dominic (European Journal of Transport and Infrastructure Research, 2002)
The European Commission provides an important source of funding for research and development in many sectors including transport. Recent analysis indicates that the European Commission currently funds almost a quarter of all publicly financed research and development projects in the European Union (Schelhowe, 2002). The vast majority of European research funding comes from the EU’s research ‘framework programmes’: multiannual programmes for research, technological development and demonstration (RTD) activities. The current framework programme, the Fifth Framework Programme (FP5), sets European research priorities for RTD activities up to 2002. Beyond 2002, a new framework programme, the Sixth Framework Programme (FP6), will set EU research priorities. Preparations are now well underway within the European Commission for this new framework programme, which will identify European research priorities for RTD activities up to 2006. At the time of writing (early 2002), the European Commission is close to adopting proposals regarding the specific programmes and the implementation of FP6. This article examines the draft proposals for FP6 and identifies the prospects for transport research funding from the European Commission over the next few years. Of course it is possible that the content of the Sixth Framework Programme will not exactly match the draft proposals reported in this paper although it is most unlikely that any of the main areas of research will change.